Development of Cross-Cultural Communication in International Tourism - AZAROVA, Ofeliia Andranikovna; GORYACHEVA, Ekaterina Nikolaevna; ILKEVICH, Sergey Viktorovich; SEVRYUKOVA, Oksana Ivanovna; STAKHOVA, Liudmila Viacheslavovna (Journal of Environmental Management and Tourism, 2020)
The article is devoted to the aspects of cross-cultural communication in international tourism. It has been established that international tourism remains almost the only source of direct communication between representatives of different cultures in the information age of developed Internet communications and virtual reality, as a result of which the consciousness and self-consciousness of a person radically changes. It has been revealed that cross-cultural communication in international tourism becomes the basis for the exchange of values and experiences between different cultural worlds and their mutual implication, an integral feature and dominant of the international tourism business. It has been proved that the modern scientific discourse of cross-cultural communication in international tourism covers a wide range of concepts in various social dimensions, such as globalization, mobility, mass movement of people and creation of new cultural communities.